Diagnosis of bacterial endophthalmitis by broad-range quantitative PCR. Issue 3 (31st July 2010) - Sugita, Sunao; Shimizu, Norio; Watanabe, Ken; Katayama, Miki; Horie, Shintaro; Ogawa, Manabu; Takase, Hiroshi; Sugamoto, Yoshiharu; Mochizuki, Manabu
Abstract : Aim: To measure the bacterial genome in ocular fluids and to analyse the clinical relevance of infectious endophthalmitis. Methods: Nineteen ocular fluid samples (eight aqueous humour and 11 vitreous fluid samples) were collected from 19 patients with suspected bacterial endophthalmitis. Fifty ocular samples from uveitis patients were also collected along with 40 samples from patients without ocular inflammation and used as controls. Bacterial ribosomal DNA (16S rDNA) was measured by a quantitative PCR assay. Results: Bacterial 16S rDNA was detected in patients with clinically suspected bacterial endophthalmitis (18/19, 95%). With the exception of one case, high copy numbers of bacterial DNA were detected (1.7×10 3 –1.7×10 9 copies/ml) in these patients. There were 10 samples (53%) with positive bacterial cultures while there were nine samples (47%) with positive Gram-staining. Real-time PCR detected bacterial 16S rDNA in three (6%) of the 50 samples from the control uveitis patients. In addition, none of the samples from the control patients without intraocular inflammation were positive. Conclusions: Quantitative broad-range PCR of bacterial 16S rDNA is a useful tool for diagnosing bacterial endophthalmitis.